Platelet bioenergetics correlate with skeletal muscle respiration in a murine model of type II diabetes - Wilkinson, Mia S.; Ferguson, Emily J.; Bureau, Justin; Haggerty-Goede, Roan A. L.; Miller, Dalia M.; Kuriakose, Michelle; Veeneman, Jennifer L. M. H.; Lima, Patricia D. A.; McGlory, Chris; Dunham-Snary, Kimberly J. (Frontiers in Molecular Biosciences, 2025)
Mitochondrial bioenergetic research in skeletal muscle is limited by the need for biopsies. We executed a proof-of-concept study to evaluate whether blood platelets could serve as a minimally invasive surrogate for skeletal muscle mitochondrial respiration in mice. Using Seahorse extracellular flux analysis, platelet respiration was measured in healthy C57BL/6J and leptin receptor-null db/db mice, while high-resolution respirometry (Oroboros O2k) assessed mitochondrial function in white gastrocnemius muscle of the same animals. A critical component of this study was extensive methodological optimization for platelet bioenergetics analysis in mice. We provide comprehensive methodological details and guiding principles for performing Seahorse bioenergetic assays on mouse platelets. Our foundational findings also suggest platelet mitochondria can reflect tissue-level mitochondrial health, pointing to a potential “liquid biopsy” approach for assessing metabolic status. Multiple key metrics of respiration showed significant correlations between platelets and muscle in the same animals, indicating that platelet bioenergetic profiles mirror the metabolic status of skeletal muscle in healthy and genetically diabetic mice. This work lays the conceptual and methodological foundation for future studies in human metabolic diseases where muscle bioenergetic dysfunction is implicated but current methods are not implementable for clinical surveillance. This study provides foundational proof-of-concept in healthy and diabetic mice, motivating validation in human studies as the next step toward biomarker development and precision medicine strategies.